2008
DOI: 10.1007/s11065-008-9053-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temporal Lobe Lesions on Retrograde Memory: A Critical Review

Abstract: Scientific interest in retrograde memory has grown considerably over the last two decades. Studies have demonstrated that several brain regions, including the temporal lobes, participate in the formation, maintenance and storage of past memories. Different patterns and extents of retrograde memory deficits have been recorded in patients with temporal lobe lesions. It has been argued that the pattern of retrograde memory deficits is determined not only by the side and specific location of lesion within this reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 147 publications
(174 reference statements)
2
28
0
Order By: Relevance
“…there were fewer retrograde amnesia tests available for psychologists; causes of retrograde amnesia were beyond experimenter control; few cerebral pathologies presented with focal or isolated symptoms of retrograde amnesia; and retrograde amnesia was comparatively neglected in research with animals, functional imaging and computational modelling when compared with anterograde amnesia (impairment of new learning). More recently, Lah and Miller [7] reviewed currently available retrograde amnesia measures. Although identifying a range of tools or techniques, including the dead/alive test [8], autobiographical memory interview (AMI) [9], the cued recall technique [10] and the use of famous faces-based measures [11], there was no discussion of how retrograde amnesia measures could be affected by, or used to identify, malingered impairment.…”
Section: Recent Findingsmentioning
confidence: 99%
“…there were fewer retrograde amnesia tests available for psychologists; causes of retrograde amnesia were beyond experimenter control; few cerebral pathologies presented with focal or isolated symptoms of retrograde amnesia; and retrograde amnesia was comparatively neglected in research with animals, functional imaging and computational modelling when compared with anterograde amnesia (impairment of new learning). More recently, Lah and Miller [7] reviewed currently available retrograde amnesia measures. Although identifying a range of tools or techniques, including the dead/alive test [8], autobiographical memory interview (AMI) [9], the cued recall technique [10] and the use of famous faces-based measures [11], there was no discussion of how retrograde amnesia measures could be affected by, or used to identify, malingered impairment.…”
Section: Recent Findingsmentioning
confidence: 99%
“…In particular, several studies have demonstrated that when damage extends into the lateral temporal cortex, retrograde amnesia for autobiographical memory affects both recent and remote memory (23)(24)(25). In a comprehensive review of studies finding impaired autobiographical memory (26), 54% found that the impairment extended into the remote past. When patients were excluded if they had damage beyond the MTL, 9% of studies found such an extended impairment and 91% found retrograde amnesia to be temporally graded.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of retrograde amnesia that have examined memory for both item familiarity and for recall of associations (e.g., Reed and Squire, 1998; Bright et al, 2006; see Lah and Miller 2008 for a review of studies of retrograde memory) have shown mixed results, with item familiarity sometimes impaired along with recall (e.g., Eslinger, 1998) and sometimes spared despite impaired recall (e.g., Cipolotti et al, 2001). Our studies focus on LSJ's knowledge of associations between images and names, sounds and names, and questions and answers; but failure with these stimuli could stem from forgetting of items or associations.…”
Section: Discussionmentioning
confidence: 99%
“…Two such areas of knowledge have been especially widely-used: famous people (names, faces, professions) and major public events (e.g., Reed and Squire, 1998; Steinvorth et al, 2005). For example, in a review 50 years of studies of retrograde memory deficits following temporal lesions, Lah and Miller (2008) analyzed 90 patients in 62 studies of retrograde memory testing autobiographical memories, memories for public events, or memories for famous people (for details see Table 1 in Lah and Miller, 2008). Remarkably, only 5 of the 62 studies tested an area of general world knowledge other than famous people or events, highlighting the heavy reliance on this circumscribed kind of knowledge in studies of retrograde amnesia.…”
Section: Introductionmentioning
confidence: 99%